Did political constraints bind during transition? Evidence from Czech elections 1990 - 2002 - Orla Doyle; Patrick Paul Walsh (Institute for the Study of Labor (IZA), 2005)
Many theoretical models of transition are driven by the assumption that economic decision making is subject to political constraints. In this paper we empirically test whether the winners and losers of economic reform determined voting behaviour in the first five national elections in the Czech Republic. We propose that voters, taking stock of endowments from the planning era, could predict whether they would become winners or losers of transition. Using survey data we measure the percentage of individuals by region who were afraid and not afraid of economic reform in 1990. We define the former as potential winners who should vote for pro-reform parties, while latter are potential losers who should support left-wing parties. Using national election results and regional economic indicators, we demonstrate that there is persistence in support for pro-reform and communist parties driven by prospective voting based on initial conditions in 1990. As a result, we show that regional unemployment rates in 2002 are good predictors of regional voting patterns in 1990.
Keywords: D72; E24; E61; 330; political constraints; prospective economic voting; initial conditions; Systemtransformation; Wahlverhalten; Regionale Arbeitslosigkeit; Tschechische Republik